Isolated abducens nerve palsy induced by vincristine therapy - (:unkn) unknown (My University, 2004)
We report a 28-year-old man with non-Hodgkin's lymphoma who presented with acute onset of diplopia 3 weeks after the completion of combination chemotherapy with vincristine. He had a left esotropia with marked decrease in abduction. Magnetic resonance imaging scan of the brain showed thickening and enhancement of the left abducens nerve. Lymphomatous and other intracranial pathologies were excluded, and vincristine neurotoxicity was considered as the possible etiology of the abducens nerve palsy. His diplopia improved gradually, then completely resolved 4 weeks after the cessation of vincristine therapy. We concluded that isolated ocular muscle paresis can be the presenting sing of a toxic neuropathy associated with vincristine use.
Keywords: Adult; Humans; Treatment Outcome; Male; Visual Acuity; Magnetic Resonance Imaging; Diplopia; Antineoplastic Agents, Phytogenic; Lymphoma, Non-Hodgkin; Abducens Nerve; Abducens Nerve Diseases; Vincristine